New insights into the role of ribonuclease P protein subunit p30 from tumor to internal reference - Wu, Junchao; Yu, Sijie; Wang, Yalan; Zhu, Jie; Zhang, Zhenhua (Frontiers in Oncology, 2022)
Ribonuclease P protein subunit p30 (RPP30) is a highly conserved housekeeping gene that exists in many species and tissues throughout the three life kingdoms (archaea, bacteria, and eukaryotes). RPP30 is closely related to a few types of tumors in human diseases but has a very stable transcription level in most cases. Based on this feature, increasing number of studies have used RPP30 as an internal reference gene. Here, the structure and basic functions of RPP30 are summarized and the likely relationship between RPP30 and various diseases in plants and human is outlined. Finally, the current application of RPP30 as an internal reference gene and its advantages over traditional internal reference genes are reviewed. RPP30 characteristics suggest that it has a good prospect of being selected as an internal reference; more work is needed to develop this research avenue.